Evaluation of Nutrient Dosing Methods for Hydroponic Crop Cultivation - Prastono, Haryo; Solahudin, Mohamad; Supriyanto (Jurnal Keteknikan Pertanian, 2023)
The application of control systems for hydroponic cultivation in greenhouses has developed rapidly, and one of them is the nutrient-dosing control system. Various nutrient dosing control systems, such as on/off, fuzzy logic, and K-NN, have been widely discussed by many researchers. Nevertheless, there has been limited discourse regarding the employed dosing methods, namely sensor-based nutrient dosing and nutrient dosing based on the nutritional dilution equation. The objective of this study was to assess the effectiveness and efficiency of three nutrient dosing methods that can be used in control systems: nutrient dosing based on nutrient dilution equations (method α), sensor-based (method β), and a mixed nutrient dosing method combining the two previous methods (method γ). This research begins by identifying several nutrient dosing methods that can be used in control systems. After that, the dosing methods were tested, and data analysis was carried out. Based on the three methods proposed in this study, method γ has the best results with a mean absolute percentage error (MAPE) of 0.77% and a root mean square error (RMSE) of 4.3, respectively, in relation to the targeted concentration of the nutrient solution. Method β has slightly higher results, with a MAPE of 0.82% and an RMSE of 4.62. Method α has the worst results, with a MAPE of 13.42% and a RMSE of 74.98. However, if the desired target nutrient concentration is less than 300 ppm, method β is the most suitable option compared to the other methods.